Migration and Christian identity in Congo (DRC) - Wild-Wood, Emma. (Studies of Religion in Africa, 2008)
Christianity and migration have greatly influenced society and culture of sub-Saharan Africa, yet their mutual impact is rarely studied. Through oral history research in north eastern Congo (DRC), this book studies the migration of Anglicans and the subsequent reconfiguring of their Christian identity. It engages with issues of religious contextualisation, revivalism and the rise of Pentecostalism. It examines shifting ethnic, national, gender and generational expressions, the influence of tradition, contemporanity, local needs and international networks to reveal mobile group identities developing through migration. Borrowing the metaphor of 'home' from those interviewed, the book suggests in what ways religious affiliation aids a process of belonging. The result is an original exploration of important themes in an often neglected region of Africa.